Designing a Skill Tree Model for Learning Media - Fanani Arief Ghozali; Rustam Asnawi; M Khairudin; Mentari P Jati; Ahmad Hoirul (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
In a modern era, digital media has been created and used for educational purposes. In the educational programs, teachers have many objectives which can be converted into some important points that can be mapped on a skill tree. A skill tree is actually commonly known for building gaming media as a decision making system but it has not been widely applied for educational purposes. This paper discusses how to design a skill tree model for effective learning media. The learning objective can be mapped in the skill tree and used for decision-making to decide whether the subject matter being taught by a teacher can proceed or not. The method used in this study was the development method. The findings indicated that the skill tree can be applied as learning media. The results of product testing reveal insignificant defects and smooth operation. Therefore the developed software can be considered as an eligible product to be applied. This software is aimed to assist teachers in understanding the weaknesses of the students and improving the quality of education.